PELATIHAN PENDIDIKAN KARAKTER BERBASISKAN BUDAYA LOKAL SEBAGAI ANTISIPASI KENAKALAN REMAJA PADA GURU-GURU DAN SISWA-SISWI SMP UTAMA 3 BANDAR LAMPUNG - Nurdin, Bertoven Vivit; Wirawan, Bintang; Sidemen, I Gede; Fatimaningsih, Endry (Prosiding Pengabdian FISIP Unila, 2012)
The idea of this service activities originated from a number of research by a team of local culture that is in Lampung. The local culture has the potential of local wisdom that has values that benefit society. We beranalisis that local knowledge can be used as social capital in the life of Indonesian people today are still prone to conflict, violence and even juvenile delinquency. Character education is one way for the inclusion of local knowledge imparted to the younger generation as the hope that the change could be made. So the dedication is to introduce a new approach to education that is based on the character of the local culture in anticipation of juvenile delinquency. The method of devotion is to lectures, and discussions with teachers in junior MAIN 3 Bandar Lampung. By trying to introduce this approach to teachers at the school. The aim is that teachers have the knowledge and be able to integrate the local culture in the implementation of character education in schools. From the results obtained training increased 20 points (score 0-10) from initial knowledge to science after doing the training. This dedication results indicated very good. Keywords: character education, local culture, teen delinquency.